Pengembangan Media Pembelajaran Dasar Listrik dan Elektronika Berbasis Mind Mapping - Debi Kumala Buana Putri; Dwiprima Elvanny Myori (Jurnal Pendidikan Teknik Elektro, 2020)
The implementation of this research aims to develop valid and praticial mind mapping based learning media in basic electricity and electronics (DLE) subjects. This study used the R&D (Research and Development) method. Subjects in this study were students X TITL SMK Mumammadiyah 1 Padang who were registered in semester 1 of the 2020-2021 academic year. This research was tested by three validators consisting of one teacher of basic subjects of electricity and electronics at the vocational high school where the study was coducted, and two validators from the lecturer of the departement of elektrical engineering faculty of engineering Universitas Negeri Padang with the results of media validator of 86% with the valid category. In the practicality test, the respondents were subject teacher and class X TITL student with a response of 86% from the teacher and an average 84,28% of student stated that mind mapping based DLE learning media was very practical. It was concluded that the basic learning media for electricity and electronics based on mind mapping were valid and practical for use in the learning process of basic electricity and electronics.